Obsuzhdenie Ukaza o gosprestupleniiakh . Obsuzhdenie Ukaza o gosprestupleniiakh . Debate on the Edict on Treason . Обсуждение Указа о госпреступлениях - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Program discussing the changes made to Article 70 of the Criminal Code. Featured in the program: Reshetov, IUrii Aleksandrovich (Head of the Ministry of Foreign Affairs); Kudriavtsev, Vladimir Nikolaevich (Academician) Contributors: Orlov, Petr (Anchor); Itkin, Vladimir (Anchor) Обсуждение новой формулировки статьи 70 Уголовного кодекса. В программе участвуют: Решетов, Юрий Александрович (Глава Министерства иностранных дел); Кудрявцев, Владимир Николаевич (Академик) Создатели: Орлов, Петр (Ведущий/Ведущая); Иткин, Владимир (Ведущий/Ведущая)